2016
DOI: 10.1093/occmed/kqw022
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting finger and hand pain in workers with HAVS

Abstract: Background Pain and its management are important aspects of hand-arm vibration syndrome (HAVS). Aims To determine the factors associated with finger and hand pain in workers with HAVS and, specifically, to assess the impact of several neurological variables as well as the vascular component of HAVS, grip strength and age. Methods We assessed men with HAVS at a hospital occupational medicine clinic over 2 years. Subjects scored finger and hand pain separately using the Borg Scale (0–10). The possible predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
4
16
0
Order By: Relevance
“…Once injuries progress to this point, there is loss of sensory function and a decline in manual dexterity. The diminished dexterity exerts significant effects on quality of life with workers being unable to perform tasks that require fine motor coordination, such as buttoning a shirt (House, Krajnak, and Jiang 2016). Consequently, several investigations focused on finding engineering (Hewitt et al 2015; Krajnak et al 2015; McDowell et al 2016; Welcome et al 2016) or managerial (Cherniack et al 2004; Krajnak et al 2014) controls that diminish exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once injuries progress to this point, there is loss of sensory function and a decline in manual dexterity. The diminished dexterity exerts significant effects on quality of life with workers being unable to perform tasks that require fine motor coordination, such as buttoning a shirt (House, Krajnak, and Jiang 2016). Consequently, several investigations focused on finding engineering (Hewitt et al 2015; Krajnak et al 2015; McDowell et al 2016; Welcome et al 2016) or managerial (Cherniack et al 2004; Krajnak et al 2014) controls that diminish exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon previous observations (Govindaraju et al 2006b; Krajnak et al 2016; Matloub et al 2005), peripheral sensorineural function might return to pre-injury levels if exposure to vibration is terminated for a period of time in an otherwise healthy worker. However, in workers where symptoms developed or progressed to the point where there is a reduction in sensory function and loss of manual dexterity, recovery of normal function usually does not occur (Cherniack et al 2004; House, Krajnak, and Jiang 2016). Therefore, in jobs where workers are exposed to hand-transmitted vibration, having a marker or test that might be used to identify changes in sensorineural function may be critical for early detection of an injury.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examining the effects of lower frequency vibration (10–60 Hz) have found that vibration at these lower frequencies is transmitted to the elbow, shoulder, wrist and neck (Bovenzi 2015, 2006; Bovenzi, Fiorito,Volpe 1987; Bovenzi, Petronio,DiMarino 1980; Bovenzi et al 2005). Exposures at these frequencies also result in faster fatigue of the muscles of the upper arm and shoulder (Tachi et al 2004; Stewart, Taneja,Medow 2007) and reports of increased discomfort (Wyllie,Griffin 2007; Thuong,Griffin 2011; Huang,Griffin 2014; Bovenzi,Hulshof 1999; Griffin,Bovenzi 2002; Zeeman et al 2015; House, Krajnak,Jiang 2016). This has lead researchers and other members of standards committees to suggest that the frequency weighting curve should be revised, and either different curves should be generated for different tools, or different curves should be generated for different portions of the hand-arm system (Bovenzi, Lindsell,Griffin 2000; Dong et al 2001; Griffin, Bovenzi,Nelson 2003; Organization 2005; Morioka,Griffin 2010).…”
Section: Models For Assessing Health Effectsmentioning
confidence: 99%
“…However, inflammation, oxidative stress and changes in gene expression are more pervasive with exposure at or near the resonant frequency (Govindaraju et al 2006; Krajnak, Miller, et al 2012; Krajnak et al 2016; Loffredo et al 2009; Matloub et al 2005; Yan et al 2005). Data collected in human and animals studies have been used to improve the diagnosis of HAVS (House, Krajnak,Jiang 2016; Poole, Mason,Harding 2016; Kao et al 2008; Terada et al 2007; Krajnak et al 2007), improve tool and glove design (Welcome et al 2016; Krajnak et al 2015; Hewitt et al 2015; Dong et al 2014; Xu et al 2011), and help modify standards that suggest limitations regarding exposures based on the frequency, amplitude and duration of hand-tool use (Kwong et al 2001; Dong, Welcome,Wu 2005; Dong et al 2012; Bovenzi, Petronio,Di Martino 1980; Bovenzi, Griffin,Hagberg 2008; Bovenzi 2010).…”
Section: Models For Assessing Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation